Multiple Myeloma Experiences and Preferences: A Mixed Methods Study of Patients and Care Partners in the United States - Flora DR; Byrd R; Platt DA; Hlavacek P; Hoag Goldman E; Cappelleri JC; Kennedy CT; LeBlanc TW (Patient Preference and Adherence)
Darcy R Flora,1 Rachel Byrd,1 Daniel A Platt,1 Patrick Hlavacek,2 Erinn Hoag Goldman,2 Joseph C Cappelleri,3 C Todd Kennedy,4 Thomas W LeBlanc5 1Gryt Health Inc, Rochester, NY, USA; 2Pfizer Inc, New York, NY, USA; 3Pfizer Inc, Groton, CT, USA; 4Independent patient and research advocate, Coto de Caza, CA, USA; 5Division of Hematologic Malignancies and Cellular Therapy, Duke University School of Medicine, Durham, NC, USACorrespondence: Patrick Hlavacek, HTA, Value and Evidence, Hematology, Global Access and Value – Oncology, Pfizer Inc, 66 Hudson Blvd E, New York, New York, USA, Email Patrick.Hlavacek@pfizer.comPurpose: Multiple myeloma (MM) is characterized by treatment relapse and resistance, requiring sequential treatment decisions throughout its course. To understand how disease status and an evolving treatment landscape impact decisions made by patients and care partners, a non-interventional mixed methods study was conducted.Patients and Methods: Patients self-reporting MM and care partners were recruited through the Gryt Health Cancer Community, social media, and snowball sampling to participate in this US-based study centered around a semi-structured interview. Patients were stratified by disease refractoriness to proteasome inhibitors, immunomodulatory drugs, and anti-CD38 antibodies.Results: Participants included 32 patients (75.0% diagnosed before age 60 years) and 10 care partners. The treatment landscape for MM has significantly changed over the years with increased complexity leading patients to seek specialist involvement earlier in their treatment. When rating factors influencing treatment decisions, participants prioritized extending remission and survival while improving quality of life. As patients progressed further from diagnosis, treatment decision-making became more collaborative, with patients exhibiting increased self-advocacy. Given the rapidly changing treatment landscape, participants had difficulty finding accurate, trustworthy, and easy-to-understand information. Younger patients were in a different life stage than the average patient with MM and expressed unique concerns and support needs (ie, reproductive health and future earnings). Aside from MM specialists, advocacy organizations and support groups played prominent roles in dispersing information that patients trusted and found empowering.Conclusion: MM patients and care partners played an active role in treatment decision-making. Collaborative discussions between clinicians, patients, and care partners are crucial for building trust and empowering patients. Reliable information and support resources including those for younger patients are essential for addressing the changing needs of patients and care partners. Understanding the evolving care journey is necessary to support patients with MM to optimize treatment success.Keywords: decision-making, patient preferences, caregivers, treatment options, quality of life, qualitative research